Maternal Immune Activation and Related Factors in the Risk of Offspring Psychiatric Disorders - Conway, Fiona; Brown, Alan S. (Frontiers in Psychiatry, 2019)
Maternal immune activation (MIA) at the time of gestation has been linked to increased risk of neurodevelopmental psychiatric disorders. Animal and human models have been used to evaluate the relationship between MIA and these outcomes. Given that each of these two disciplines of study have their benefits and limitations, a translational perspective is expected to illuminate more than by the use of any single approach. In this paper, we discuss this translational framework and explore how it may be enhanced by the utilization of epigenetic studies and by investigating the microbiome. In this perspectives piece, we focus on the impact of epidemiologic studies, animal models, and preclinical studies in the literature on MIA as well as the potential for greater integration between fields.